Undergraduate Students’ Voices of Learning English through Online Application : Zoom Meeting Discussion - Widya Garini (Universitas Pendidikan Mandalika, 2022)
Online learning that is carried out by students with lecturers as part of the learning process during this pandemic makes students study harder. The online learning process which is different from face-to-face classroom learning makes students experience several obstacles and difficulties in participating in online learning. This study will try to voice the opinions and experiences of students while carrying out online learning through the online zoom meeting application during this pandemic. Through the questionnaire and interview methods, this narrative inquiry research will find the results of what students have felt so far. The obstacles found by the researchers were one of them that occurred in the student environment such as the internet connection network to the factor of the lecturers in the inaccuracy of time in teaching so that they spent learning time which made students experience some difficulties in living it. On the other hand, students also admit that online learning is positive, which is a solution to flexibility and time effectiveness during online learning through the online zoom meeting application. This online learning does have positive and negative sides from the views of students that lecturers and others need to know.